Pemanfaatan Jerami Sisa Produk Pertanian sebagai Bahan Dasar Produksi Etanol Secara Fermentasi (Optimasi Produksi Berdasarkan Perbedaan Konsentrasi Inokulum dan Lama Fermentasi) - Akmal Djamaan; Mahrani Napitupulu; Krisyanella Krisyanella (STIFARM Padang, 2009)
Research about exploiting of straw as component of ethanol as fermentation based on difference able of inoculums consentration and fermentation time has been studied. Straw utilized in this research is result of agriculture raffle from rice plant type IR 46, which taken away from rice field the district of Lubuk Minturun, Padang. The first, stage hydrolysis was done to straw using H2SO4 P 1% with various time 30, 60, 120, 180 and 240 minute and determined glucose produced for each sample. The fermentation of ethanol by using Saccharomyces cereviceae bacterium were conducted at temperature 30ºC with speed 100 rpm. Sampling was taking every 6 hours (6, 12, 18, 24, 30, 36, 42, 48, 54, 60, 66). The inoculum’s grade level is variation by 1, 2, 3% v/v. Results showed that the optimum hydrolysis time wich mark by highest glucose rate is minute 240 with grade level 0.7765 %. The highest ethanol grade of which can be yielded with inoculum 1% was 0.02066 % v/v at yeast inoculum 2 % was of 0.02549 % v/v and yeast inoculum 3 % was of 0. 07804 % v/v.